Integrated multidisciplinary approach to hidradenitis suppurativa in clinical practice - Assia Timila Touhouche, Resident; Benoit Chaput, MD, Phd; Rose Marie Rouquet, MD; Emilie Montastier, MD; Philippe Caron, MD, Phd; Yvon Gall, MD; Christian Aquilina, MD; Serge Boulinguez, MD; Marie Claude Marguery, MD; Françoise Giordano-Labadie, MD; Juliette Mazereeuw, MD, Phd; Carle Paul, MD, Phd; et al. (Wolters Kluwer, 2020)
Background: The European hidradenitis suppurativa (HS) guidelines recommend a multidisciplinary approach for patients with HS and management of comorbidities. Objective: We aimed to describe the organization of a multidisciplinary HS program and characterize the patient population. Methods: We conducted a retrospective study of patients with HS undergoing prospectively defined multidisciplinary work-up including examinations by a dermatologist, plastic surgeon, smoking specialist, and nutritionist in our outpatient unit between October 2015 and January 2017. Results: The study included 49 patients with a sex ratio of 1:1. A total of 73.4% of patients were smokers, 20.4% were overweight, 48.9% were obese, and 30.6% had symptoms of depression. The mean Sartorius score was 30.4 (±17.6). The outcome of plastic surgery consultation was as follows: 16 patients had operations, 5 were excluded based on medical history, 9 refused surgery, and 16 remained undecided. The refusal rates for consulting with the smoking cessation and nutrition specialists were 55.8% and 69.5%, respectively. Twelve patients received antibiotics, 9 received biologics, 9 underwent medico-surgical treatment, 9 underwent surgery, and 10 were lost to follow-up. The mean visual analogue scale score for satisfaction was 8.3 (±1.6; n = 28). Conclusion: An integrated multidisciplinary care model for HS is associated with high patient satisfaction. Adherence to the proposed comorbidity management was higher in female patients and related to empathetic interactions with physicians.